2004
DOI: 10.1139/l04-084
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spectral dynamic analysis of guyed towers. Part II: Manitoba towers case study

Abstract: Dynamic response of large complex space structures under wind loading is important in terms of performance and safety. Conventional method of wind loading calculation has been used successfully in codes to analyze large space structures. The method can be applied by approximating the air pressure, induced by wind, on the surfaces of structures. Although this replaces a wind loading test using complicated wind tunnel tests for any structural systems, the accuracy of the method, in the case of complex geometry g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The supporting towers can be in the form of lattice steel towers or pole-type structures. Most of the previous studies which investigated the dynamic behavior of transmission line systems under wind loads focused on conductors and on lattice steel towers as the main supporting system (Momomura et al, 1997; Horr et al, 2004). Loredo-Souza and Davenport (1998) concluded that the aerodynamic damping of the conductors has a major effect on the dynamic behavior of transmission line structures.…”
Section: Introductionmentioning
confidence: 99%
“…The supporting towers can be in the form of lattice steel towers or pole-type structures. Most of the previous studies which investigated the dynamic behavior of transmission line systems under wind loads focused on conductors and on lattice steel towers as the main supporting system (Momomura et al, 1997; Horr et al, 2004). Loredo-Souza and Davenport (1998) concluded that the aerodynamic damping of the conductors has a major effect on the dynamic behavior of transmission line structures.…”
Section: Introductionmentioning
confidence: 99%
“…wind loads and earthquakes. [5][6][7] Because of complex geometrical configurations, the dynamic characteristics of towers are nonlinear in character. Due to the power cable's vibration, dynamic loadings are generated in the transmission towers that lead to the failure of transmission tower.…”
Section: Introductionmentioning
confidence: 99%
“…Most vibration studies on transmission line systems are conducted on transmission towers under wind loads [2][3]. Transmission towers are severely excited due to the effect of wind as well as earthquake.…”
Section: Introductionmentioning
confidence: 99%